Reading the world
Western and non-Western, classic and contemporary, longer and shorter, verbal and visual, accessible and challenging. With 72 readings by thinkers from around the worldPlato to Toni Morrison, Lao Tzu to Aung San Suu KyiReading the World is the only great ideas reader for composition students that offers a truly global perspective. The Second Edition offers more contemporary readings and provides more help to make the texts accessible for undergraduate readers. Brief overviews of each reading give students a sense of what the piece is about, and detailed headnotes call attention to the rhetoric of each reading to help students focus not only on what the authors say but also on how they say it